A Study on the Impact of Reward Programs on Building Brand Loyalty for Buffet Restaurants and Perception of Environmental Value - กิติเวียง รมยพร; จั่นจินดา จุฑารัตน์; ขันทะวงค์ พรชัย; เดชจิรมณี ชัชชติภัช; พิพัฒน์พงศ์อำไพ อาทิตยา; ประวิตรางกูร ศรัณย์ (วารสารนวัตกรรมธุรกิจ การจัดการ และสังคมศาสตร์, 2024)
This study explores the impact of reward programs on building brand loyalty and enhancing the perception of environmental value among consumers of buffet restaurants in Bangkok and its vicinity. With intense competition and rising raw material costs in Thailand’s restaurant industry, reducing food waste while fostering customer loyalty is vital. The research employs a quantitative approach, utilizing survey data from 428 consumers, categorized by reward type and frequency of visits. Structural Equation Modeling (SEM) reveals that rewards and brand engagement significantly influence both intrinsic and extrinsic motivations, leading to higher participation in loyalty programs. Findings indicate that different reward types (restaurant vs. shopping mall coupons) and visit frequencies affect the perceived effectiveness of loyalty programs. Consumers receiving restaurant coupons emphasize environmental value and brand engagement as key to loyalty, whereas those with shopping mall coupons focus more on the loyalty program itself. The study concludes that integrating rewards, motivations, and sustainability into loyalty programs not only boosts customer engagement but also supports environmental sustainability. These insights suggest that effective loyalty programs in buffet restaurants should balance rewarding consumer participation and promoting sustainable practices, contributing to both brand loyalty and environmental awareness. This research provides a framework for businesses to develop strategic loyalty programs that align with consumer behavior and environmental goals, offering a pathway to long-term sustainability and profitability in the restaurant sector.